Expert System For Identifying Hemorrhoidal Disease (Hemorrhoid) Using The Certainty Factor Method - Hadi Nata, Difran; Maryaningsih, Maryaningsih; Sartika, Devi (Jurnal Komputer Indonesia, 2023)
Hemorrhoidal disease (hemorrhoids) is more common in men and the peak occurrence of hemorrhoids is at the age of 35 to 65 years and rarely occurs at the age of under 20 years which is caused by inflammation and widening of the veins around the anus originating from the plexus. hemorrhoidal. Implementation of expert systems in the health and medical fields in the form of initial diagnosis, handling of diagnosis results, determining visible clinical symptoms. Rafflesia Hospital Bengkulu is one of the general hospitals in the Bengkulu area which is located on Jl. Mahogany No 10. Rafflesia Hospital Bengkulu has many patients every day, patients who want treatment or consultation must take a queue number and schedule first, if the patient does not get a queue number on that day they will be transferred to the next day. Seeing the weaknesses in this aspect, an expert system was designed to diagnose hemorrhoids using the Certainty Factor method. This expert system was designed using the PHP programming language and MySQL database. The expert system created can make it easier for patients to have initial consultations regarding hemorrhoids (hemorrhoids) before meeting a doctor directly.